PENGARUH PEMBELAJARAN E-LEARNING MENGGUNAKAN GOOGLE CLASSROOM TERHADAP HASIL BELAJAR SISWA - Mustofa Yusli Hidayat; Firman Jaya; Tri Astindari (STKIP PGRI Situbondo, 2021)
Abstract : The purpose of this study was to determine the effect of E-Learning learning using Google Classroom on student learning outcomes in computer systems subjects at SMK Khamas Asembagus for the 2020/2021 academic year. This type of research is quantitative. The subjects of this study were students of class X TKJ 1 at SMK Khamas Asembagus which consisted of 25 students. Data collection techniques in this study were observation, interviews, documentation and questionnaires. Data analysis in this study used simple linear regression analysis with t-test. The results of data analysis show that there is an effect of E-Learning learning using Google Classroom on Computer Systems subjects at SMK Khamas Asembagus for the 2020/2021 academic year. This is indicated by the results of simple linear regression and regression coefficient testing with t-test. The results of linear regression are Y=53.027-0.373X, which means that the correlation between variable X and variable Y is low and the results of the t-test are tcount > ttable or 2,093 > 2,069, which means H1 is accepted and H0 is rejected.Keywords: E-Learning Learning, Google Classroom, Learning Outcomes Abstrak : Tujuan penelitian ini adalah untuk mengetahui pengaruh pembelajaran E-Learning menggunakan Google Classroom terhadap hasil belajar siswa pada mata pelajaran sistem computer di SMK Khamas Asembagus tahun pelajaran 2020/2021. Jenis penelitian ini adalah kuantitatif. Subjek penelitian ini adalah siswa kelas X TKJ 1 di SMK Khamas Asembagus yang terdiri dari 25 orang siswa. Teknik pengumpulan data dalam penelitian ini adalah Obsevasi, Wawancara, Dokumentasi dan Angket. Analisis data dalam penelitian ini menggunakan analisis regresi linier sederhana dengan uji-t. Hasil analisis data menunjukkan bahwa ada pengaruh pembelajaran E-Learning menggunkan Google Classroom pada mata pelajaran Sistem Komputer di SMK Khamas Asembagus tahun pelajaran 2020/2021. Hal ini ditunjukkan dengan hasil regresi linier sederhana dan pengujian koefisien regresi dengan Uji-t. Adapun hasil regresi linier yaitu Y=53,027-0,373X yang artinya korelasi antara variabel X dan variabel Y rendah dan hasil Uji-t yaitu thitung> ttabel atau 2,093 > 2,069 yang artinya H1 diterima dan H0 ditolak.